Generalized pustular psoriasis in childhood (Archives of Pediatrics of Uruguay, 2025)
Introduction: generalized pustular psoriasis (GPP) is a rare form of psoriasis in childhood characterized by aseptic neutrophilic pustules. The extent of the lesions and systemic involvement give variable severity. Its diagnosis is clinical and confirmed by histopathology.Objectives: describe the diagnostic and therapeutic approach of a girl with GPP and share the questions regarding the etiology of the identified liver involvement.Clinical case: 8 years old, with no pathological history, consulted for skin lesions such as scaly and pruritic plaques on the face, neck and trunk. No mucosal involvement, no fever. It was interpreted as infected atopic dermatitis. Clinical worsening under treatment. The plaques become erythematous, with pustules inside, spreading to the limbs. Referred by the GPP, she was admitted to hospital. Pathology anatomy confirmed subcorneal pustular dermatitis. In the evolution: regular general condition, worsening of the lesions, erythroderma and fever. Leukocytosis. Skin and blood culture without development. Treatment with retinoid (acitretin) was started, the lesions improved. On the third day, increase in liver transaminases. Acitretin was discontinued due to the suspicion of adverse effects. Discharged after 20 days, clinical and paraclinical improvement. A month later a new push without systemic commitment. Acitretin was reinstated, with positive progress.Conclusions: the low frequency of GPG can lead to diagnostic delay. This case presented liver involvement as the initial systemic manifestation. The doubt that this presentation was a serious adverse effect of the retinoid confused clinicians and led to therapeutic changes.
Keywords: Psoriasis; Child